Perspektif Islam Terhadap Pluralitas Keberagamaan - Ibrahim, Soufyan (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2018)
The most fundamental thing in Islamic religiosity is tawá¸¥ Ä«d, which is the essay of God as an act that confirms that God is the one and only God, the Absolute and Transcendent Creator. The essence of tawá¸¥ Ä«d is very urgent. Neglect of tawá¸¥ Ä«d values, means destruction of religious values in Islam, because the obligation to worship Allah to obey all His commands and stay away from all His prohibitions is the spirit of tawá¸¥ Ä«d. In this construction, tawá¸¥ Ä«d is the essence of Islam and something of action is not of Islamic value without being based on true trust in God. Tawá¸¥ Ä«d should not only be treated as a theological concept, but should also be a sociological concept. This is the reason why the Qur'an defies differences based on ethnicity, race and nation and establishes ukhuwah among believers. In this religious perspective, the basics for living together in a religiously pluralistic society have been built from the beginning on a normative and historical basis at the same time.